express(x-2)/[(x^2+1)(x-1)^2] in partial fractions in its simplest form.
express 7x+4/[(x-3)(x+2)^2] as the sum of partial fraction with constant numerators
Here i am showing the answer of the first problem, the the other guy he showed to how to frame the problem that's fantastic way , i will do the remaining steps to show the answers here
plug x=3 in the above equation u will get
plug x=-2, then C=2
finally equating the coefficient of x^2 on both sides we get it as
=1/(x-3)-1/(x+2)+2/(x+2)^2 is the final answer